Potency of Creative Industry Embroidery and Weaving in West Sumatera in Developing the Common Economy - Rose Rahmidani (Universitas Negeri Padang, 2020)
The aims of this research are: 1) to describe the portrait of embroidery and weaving business in absorbing workforce in West Sumatera, 2) Exploring and formulating problems as well as mapping the needs assessment of embroidery/embroidery creative industry and Minangkabau weave. Population in this research is the entire business unit of embroidery and weaving industry in West Sumatera spread in Padang Pariaman, Agam, Tanah Datar, Sawahlunto, Padang, Payakumbuh, Bukittinggi and Pariaman, the sample is 93 business units spread in 8 regencies and cities above. This study uses a qualitative method. Data collection using survey methods, with qualitative descriptive analysis techniques. The results of this research are; 1) Embroidery and weaving business in West Sumatera are able to absorb 2.297 workforce, 2) Problems faced by embroidery and weaving business in West Sumatra can be formulated as follows: 1) Bookkeeping/finance aspect and management, 2) Production aspect, and 3) Marketing aspect